Chemical Eye Burn Injury Due to Polyester in Industrial Worker: A case report: Poster Presentation - Case Report - General practitioner - Zahira Rikiandraswida; Ayu Anggraini Kusumaningrum (Majalah Oftalmologi Indonesia, 2023)
Introduction : Chemical eye burns are common causes of work-related eye injuries. Prompt and appropriate emergency management may be the most important factor in determining the visual outcome. Case Illustration : A 50-year-old man who works in a plastic factory immediately went to the emergency room after being exposed to melted polyester in his right eye. He complained of hurt and hotness in his eye. The emergency primary survey was stable. Triage of ophthalmology was an emergency. Initial Uncorrected Visual Acuity (UCVA) was light perception with correct projections. Physical examination revealed 2nd-degree combutio on the forehead and left cheek. Anterior right eye examination revealed palpebral edema, polyester debris on the eyelid, conjunctival mixed injection, ischemia of less than 1/3 of the limbus, corneal edema, corneal opacity, and polyester sticking to the cornea. The damage was determined as Roper-Hall grade II. In the Emergency room, Eye was immediately irrigated with 1 L of normal saline. A referral was made to the ophthalmologist and Immediate debridement was carried out. Wide corneal erosion was found after the procedure. Treatment was continued with antibiotic eye drops, lubricant eye drops, oral vitamin, and oral analgetic. The patient had improved visual acuity to 20/20 f2 with corneal scar and opacity 1 month after surgery. Discussion : The combined management of this case consisted of ocular lavage, surgery, and medication. A Chemical Eye Burn requires immediate management to prevent extensive damage leading to visual impairment. Conclusion : Initial treatment in the emergency department and referral to the ophthalmologist can improve patient outcomes.